Clinical validation of a handheld structured light device for 3D facial morphometric - Annalisa Cappella; Alessandro D’Amelio; Riccardo Solazzo; Claudia Dolci; Jacopo Burger; Giuseppe M. Facchi; Daniele M. Gibelli; Giuliano Grossi; Raffaella Lanzarotti; Chiarella Sforza; Gianluca M. Tartaglia (Scientific Reports, 2026)
Abstract Handheld systems for three-dimensional (3D) imaging of facial soft tissues are gaining increasing attention due to their affordability, portability, and user-friendliness. However, their reliability for 3D facial analysis should be verified before being integrated into clinical and research settings. We tested a novel device, the Revopoint MIRACO Pro, on 55 adults and a mannequin head, and we compared it with two validated devices. Intra- and inter-instrument reliability for traditional anthropometric parameters was evaluated through several statistical approaches. Additionally, the Root Mean Square (RMS) point-to-point distance was calculated between 3D images acquired through the different devices. Overall, all three instruments consistently reproduced the 3D facial structure across subjects, with 25 out of 27 measurements demonstrating high intra- and inter-device agreement and non-clinically significant biases. Furthermore, surface area assessments proved highly reliable, whereas volume measurements did not, and the RMS showed clinically acceptable congruence with slight variability caused by facial mimicry and involuntary movements of participants. Despite its affordability and practicality, the Revopoint MIRACO Pro requires multiple scans around the face, causing motion artifacts that may limit its applicability in less cooperative cohorts, such as children or patients with cognitive and neurological impairments, unless further validation studies demonstrate its clinical suitabilityin these groups.